Pelaksanaan Evaluasi Ranah Afektif Pembelajaran Menulis Puisi di SMA 1 Pertiwi - Yola Yunita; Dina Fitria Handayani (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to describe the planning, implementation, and challenges of teacher evaluation in poetry writing instruction for class X E-7 at SMA 1 Pertiwi. Data were collected through observation and documentation. The analysis results indicate that affective domain assessment involves poetry appreciation, emotional expression, and student engagement in the creative writing process. This qualitative method positively impacts students’ interest and motivation, leading to increased creativity and poetry writing skills. Empirical data show that students respond well to affective domain assessment, feeling more valued and supported, which positively affects their attitude towards writing poetry. It is recommended to integrate affective domain assessment methods more widely into the curriculum, including teacher training and the development of supportive teaching materials. This research provides valuable information for teachers and other educators to improve the quality of poetry writing instruction. Affective domain assessment methods have proven effective in creating a more supportive and inspiring learning environment. This research also highlights the challenges teachers face in conducting such evaluations.